Enhanced magnetostrictive properties of Mn substituted cobalt ferrite Co1.2Fe1.8O4 - Bhame, Shekhar D.; Joy, Pattayil Alias (Journal of Applied Physics, 2006)
The effect of substitution of Fe and Co by Mn on the magnetostrictive properties of the cobalt ferrite Co1.2Fe1.8O4 has been studied and compared. The studies on Co1.2-xMnxFe1.8O4 and Co1.2Fe1.8-xMnxO4 (0 <= x <= 0.4) showed a marked dependence of magnetostriction on the substitution of both Fe and Co by Mn. Higher magnetostriction is obtained for the substitution of Co by Mn whereas the magnetostriction is reduced substantially on the substitution of Fe by Mn. Higher magnetostriction at low magnetic fields and enhancement of the strain ratio have been observed for the substitution of Co by Mn. (c) 2006 American Institute of Physics.